THE FIRST LIVER TRANSPLANTATION AT ANKARA UNIVERSITY SCHOOL OF MEDICINE - S. ERSÖZ; E. ANADOL; S. KARAYALÇIN; C. YURDAYDIN; E. ERDEN; Ö. UZUNALİMOĞLU and İ. CEYLAN (Turkish Journal of Gastroenterology, 2020)
-